An Empirical Investigation of Pension Fund Property Rights - Landsman, Wayne (The Accounting Review, 1986)
[This study empirically examines whether pension fund assets and liabilities associated with corporate-sponsored defined benefit pension plans are valued by the securities markets as corporate assets and liabilities. An equity valuation model based on the balance sheet identity is used to permit pension and non-pension assets and liabilities to have separate empirical coefficient values. This study differs from earlier ones [Feldstein and Seligman, 1981; Feldstein and Morck, 1982; and Daley, 1982, 1984] which examine how share prices are affected by the net pension liability in the context of the Litzenberger and Rao [1971] equity valuation model. Using theoretical benchmark coefficient values for pension assets and liabilities based on the Miller [1977] model of capital market equilibrium, this study finds evidence consistent with the notion that pension fund property rights-ownership of pension assets and liabilities-lie fully with the firm. Several empirical extensions are explored to examine whether the basic finding can be made more robust.]